Avascular Necrosis of Femoral Head Diagnosed by 99mTc MDP Bone Scan Incorporated with SPECT- A Case Report - Bhattacharjee, Puja; Mandal, Tapati; Quddus, Sharmin; Reza, Sharmin; Islam, Saiful; Kamruzzaman, Md; Haque, Jasmine Ara (Bangladesh Journal of Nuclear Medicine, 2022)
Avascular necrosis (AVN) may be defined as cellular death of bone components due to the lack of blood supply resulting in joint damage and loss of joint function. This condition may arise from a number of causes i.e. both traumatic and non-traumatic. Diagnosis of the disease at an early stage and deliberate management can prevent the unwanted complications like femoral head collapse and severe arthritis and may save the bone. Although diagnosis of AVN is primarily dependent on radiological investigations, the incremental value and vital role of 99mTc-methylene diphosphonate (99mTc-MDP) single-photon emission computed tomography (SPECT) over planar bone scintigraphy permits more accurate localization of lesions and provide pertinent information to recognize the disease at initial stage for better management. We present a case of unexplained low back pain in a young woman who was diagnosed as having avascular necrosis of both femoral heads by 99mTc-MDP bone scan incorporated with SPECT Bangladesh J. Nuclear Med. 23(1&2): 55-58, 2020